Effects of 6-week CKC Training on Proprioception and Electrical Activity of Some Lower Extremity Muscles in Females with Generalized Joint Hypermobility Syndrome - torkan abbasi; malihe hadadnezhad; fereshteh eftekhari (Sport Sciences and Health Research)
Effects of 6-week CKC Training on Proprioception and Electrical Activity of Some Lower Extremity Muscles in Females with Generalized Joint Hypermobility Syndrome Generalized joint hypermobility syndrome causes abnormality, knee joint injury and instability. It has also been reported to have a deficit in the joint position sense and differences in the level of muscle activity. The purpose was to determine the effect of closed-kinetic-chain training on proprioception and the electrical activity of some lower extremity muscles in hypermobile females. Twenty-four females with generalized joint hypermobility syndrome participated voluntarily in this study. The subjects were randomly divided into Control and experimental groups. The muscle activity of the some lower extremity muscles; vastus medialis, rectus femoris, vastus lateralis, semitendinosus, biceps femoris and medial gastrocnemius was measured during drop landing by surface electromyography and knee position sense error via Imaged-based goniometry. Then experimental group performed training program for six weeks. Finally Shapirovilk test and covariance was used to data analyzing. The results showed, the closed-kinetic-chain training improves proprioception and the level of feed-forward activity of the Vastus medialis, Vastus lateralis, semitendinosus and medial gastrocnemius and the feedback muscle activity of Vastus Medialis and Vastus lateralis increased significantly. We concluded, the closed-kinetic-chain training can be considered as a safe and effective training method to improve the essential factors for stability of joints in the hypermobile females. Keywords CKC training, Electromyography, Generalized joint hypermobility syndrome, instability, joint position sense